Total mechanical stapled oesophagogastric anastomosis on the neck in oesophageal cancer – prevention of postoperative mediastinal complications - Zieliński, Jacek; Jaworski, Radosław; Irga-Jaworska, Ninela; Haponiuk, Ireneusz; Jaśkiewicz, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Oesophagogastric anastomosis after oesophagus resection is commonly performed on the neck. Even though a few different techniques of oesophagogastric anastomosis have been previously detailed, both manual and mechanical procedures have been burdened with leakages and strictures. Our simple technique of oesophagogastric anastomosis is a modification of mechanical anastomosis with the use of a circular stapler in order to prevent postoperative leak and concomitant mediastinal complications. Since 2008, we have performed nine oesophagogastric anastomoses following oesophagus resection. The mean age of the operated patients was 54 years. There was no mortality among the operated patients in the early post-operative period. The mean follow-up period for the patients operated on in our department was 17 months until the time of the analysis. None of the patients showed any leakage or stricture, and no mediastinal complications were reported in the group. Following our own experience, mechanical anastomosis with the use of a circular stapler seems to decrease the time of the operation as well as significantly reducing the incidence of leakages from the anastomosis. This type of anastomosis may decrease the number of postoperative strictures and the most dangerous mediastinal infections.